Biochar and Solid Decanter Improve Selected Soil Chemical Properties and Leaf Nutrient Status of Oil Palm Seedlings under Reduced NPK Fertilization - Sakiah; Siti F Batubara; Febriana Roosmawati; Saroha Manurung; Rahmad Dian; Sigi Ardika; Adiani Y Siahaan; Riki Pradana; Bolkiah Habibie (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2026)
Oil palm seedling growth in acid mineral soils is often constrained by low soil fertility and limited nutrient retention, making organic amendments a potential strategy to improve growing media quality while reducing mineral fertilizer input. This study evaluated the effects of biochar and solid decanter, applied individually or in combination, on soil chemical properties and leaf nutrient status of oil palm seedlings under reduced compound mineral fertilizer rates. The experiment was arranged in a non-factorial randomized block design with seven treatments and four replications. The treatments were P0: without soil amendment + 100% NPK fertilizer; P1: 0.6 kg plant−1 solid decanter + 75% NPK fertilizer; P2: 0.6 kg plant−1 solid decanter + 50% NPK fertilizer; P3: 1.5 kg plant−1 biochar + 75% NPK fertilizer; P4: 1.5 kg plant−1 biochar + 50% NPK fertilizer; P5: 0.6 kg plant−1 solid decanter + 1.5 kg plant−1 biochar + 75% NPK fertilizer; and P6: 0.6 kg plant−1 solid decanter +1.5 kg plant−1 biochar + 50% NPK fertilizer. After 14 weeks of treatment application, the treatment packages significantly affected soil organic carbon, total soil nitrogen, leaf phosphorus concentration, and soil exchangeable potassium. Soil organic carbon increased from 1.33% in the control to 5.83% in the combined biochar and solid decanter treatment with 50% NPK fertilizer. Total soil nitrogen also increased from 0.13% to 0.49% under the same treatment. However, soil pH, soil available phosphorus, leaf nitrogen, and leaf potassium were not significantly affected. These findings indicate that the integrated amendment-fertilizer packages, particularly the combination of biochar + solid decanter + 50% NPK fertilizer, improved soil organic carbon and total soil nitrogen and supported selected nutrient parameters, including leaf phosphorus concentration and soil exchangeable potassium, under a 25% to 50% reduction in the recommended NPK fertilizer rate.